FLDs on Turmeric (Rajendra sonia) in Muzaffarpur, Bihar: Adoption Horizontal Spread and Satisfaction Level - Meena, M. L.; Singh, Pushpa; Kundu, M. S. (Indian Journal of Extension Education, 2021)
Keeping in view of effective extension approach of Frontline demonstrations (FLDs) for dissemination of technology FLDs on turmeric conducted by KVK, Turki, Bihar. The yield and economic performance of frontline demonstration, horizontal spread of technology, extent of adoption level and extent of satisfaction of respondent farmer over extension services and performance of demonstration was measured. It was observed that there was 15.0 to 19.6 per cent increase in fresh rhizome yield over local check and the average benefit cost ratio was higher under demonstration 3.3 as compared to control plots 2.5during the all years of the study. The horizontal spread of turmeric cv. Rajendra sonali was estimated from about 13 ha during 2015-16 to 43 ha during the year 2019-20. The findings of the study also revealed that there was increase in adoption level ranging from 9.4 per cent of sowing time and method to 46.9 per cent of improved and quality seedafter the FLD programmes. The majority of the respondent farmers expressed high extent (51.2%) to the medium (34.4%) extent of satisfaction from extension services and performance of technology under demonstrations. It can be concluded that frontline demonstrations are one of the important tool to demonstrate newly released crop productionand protection technologies and its management practices in the farmer’s field under different agro-climatic region and farming situations